Kommunikationsräume im kaiserzeitlichen Rom - Mundt, Felix (2012)
The ancient city of Rome can be understood as an ensemble of monuments, as aspace of actionfor its inhabitants, as a literary construction. Communication took place in it, about it and through it; that is by means of furnishing it with a conscious programme of buildings and works of art. From the perspective of various classical disciplines, the papers in this volume analyse the relationships between these three forms of communication about the city of Rome from the beginning of the Principate to Late Antiquity...